Immunomodulatory meaning of diet and COVID-19 - Dominika Grońska; Monika Kłujsza; Aleksandra Pelczar; Jolanta Kaszuba-Zwoińska (Medycyna Ogólna i Nauki o Zdrowiu, 2022)
Introduction and objective The latest scientific reports showed that there is a relationship between the state of the gastrointestinal tract and the immune system, and the incidence of COVID-19. Diet can exert an immunomodulatory effect and regulate the immune response of an organism. The aim of the review is to show the effects of immunomodulators contained/supplemented in a diet on the infection SARS-CoV-2 and the course of COVID-19.